2020
DOI: 10.1016/j.neuroimage.2020.116817
|View full text |Cite
|
Sign up to set email alerts
|

Can EEG and MEG detect signals from the human cerebellum?

Abstract: The cerebellum plays a key role in the regulation of motor learning, coordination and timing, and has been implicated in sensory and cognitive processes as well. However, our current knowledge of its electrophysiological mechanisms comes primarily from direct recordings in animals, as investigations into cerebellar function in humans have instead predominantly relied on lesion, haemodynamic and metabolic imaging studies. While the latter provide fundamental insights into the contribution of the cerebellum to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 105 publications
(178 reference statements)
3
70
1
Order By: Relevance
“…Another important caveat of this study is that, in MEG source-reconstructed data, the signal-to-noise ratio is heavily dependent on the depth distance between the source and the sensor, and hence is not homogeneous for all the sources. However, recent evidence showed that signals reconstructed from the basal ganglia contain reliable information about brain activity (31,32) as well as those from the cerebellum (33). On the one hand, MEG signals derived from the cerebellum are 30-to-60 % weaker as compared to the cortical surface (34).…”
Section: Discussionmentioning
confidence: 99%
“…Another important caveat of this study is that, in MEG source-reconstructed data, the signal-to-noise ratio is heavily dependent on the depth distance between the source and the sensor, and hence is not homogeneous for all the sources. However, recent evidence showed that signals reconstructed from the basal ganglia contain reliable information about brain activity (31,32) as well as those from the cerebellum (33). On the one hand, MEG signals derived from the cerebellum are 30-to-60 % weaker as compared to the cortical surface (34).…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes technological limitations may hinder essential features extraction for a successful BCI operation for an individual. For example, measurements of scalp EEG/MEG may not show good task-specific signals due to the folding of the cortex or scalp-to-cortex distance for that individual (Andersen et al, 2020 ).…”
Section: Challengesmentioning
confidence: 99%
“…Also, some studies reported the potential use of HD-EEG data (compared to low EEG channel density) in some pathological conditions such as the localization of epileptic networks 15 and the detection of cognitive decline in neurodegenerative diseases 16 . In addition, emerging evidence show the possibility, to some extent, to capture sub-cortical structures using HD-EEG 17 , 18 . In this context, the availability of task-free and task-related open-access HD-EEG databases is becoming mandatory to (i) decipher the fast (sub-seconds) reconfiguration of functional brain networks during cognition, (ii) develop new signal processing methods to adequately estimate cortical brain networks and (iii) allow the reproducibility of results obtained so far using HD-EEG.…”
Section: Background and Summarymentioning
confidence: 99%